Penerapan Pengendalian Persediaan Bahan Baku Ban dengan Model Probabilistik dan Sistem Kuantitas Pemesanan Tetap - Rizki Alfi; Muhammad Harif; Pharmayeni Pharmayeni (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2022)
Inventory of raw materials is very important for the smooth production of the company and meet consumer demand for the company in market demand. The demand for tire production fluctuates and causes the demand for products not to need to be met to order, due to the shortage of raw materials. To solve the shortage of raw materials, the company holds special orders in consideration of savings in ordering the cost of ordering messages. To overcome the shortage of raw materials, the company holds special orders or sudden orders which will increase the cost of the message. The purpose of this study is to determine the optimum ordering of raw materials to minimize total inventory costs by using a probability model of raw material inventory control with a fixed order quantity system (Q method). From the results of research using the probabilistic model of inventory control method Q method, obtained the optimal order quantity (q*), reorder point (rop), and safety stock (ss) with total inventory costs more efficient compared to the total inventory costs of the company's current policies. what is to be achieved in inventory control is to minimize the cost of ordering, and the cost of savings to the company.